BERINTERAKSIDENGAN NONMUSLIM” al-Musalimun”; PERSFEKTIF HADIS - Johar Arifin (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
This paper contains an explanation of the rules of Shari'a perspective Hadith of Prophet Muhammad SAW in interacting with non-Muslim parties in this discussion group focused on the al-Musalimun their peaceful coexistence and not hostile to Islam. This paper tried to investigate how the Prophet interact with respect to the above Qauliyah Sunnah and the Sunnah Fi'liyah, hoping to ward off negative public perception been assumed that the non-Muslim is an enemy that must be fough and was also able to provide a positive contribution to the Government , of Religion, the scholars, traditional leaders and Muslims in general, so it can be realized life in peace, safe, prosperous, spiritual and physical